TINJAUAN PELAKSANAAN ADMINISTRASI PERSEDIAAN BARANG PADA PT MAXINDO MITRA SOLUSI JAKARTA - Pater Rajagukguk; Hardani Hardani; Susanti Susanti; Bambang Haryono (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
In an organization or institution, there should be an administration procedure that control all the entire goods movement weather the aquepments or tools that are needed to the production process or the purchasing of the goods wich will be sold in the future, the inventory or return goods that are broken or complained by the customer. This research is an action research which is aiming to know the administration implementation of the inventory of the internet installation toolls in PT Maxindo Solusi Mitra Jakarta, to know the administration procedure, method, and the document used. This is aqualitative research that use interview, observation, documentation, and literature review to collect the data. The staffs that are involved in the administration procedure of the goods inventory begin from the purchasing, operational manager, warehouse supervisor, inventory administration, operational staff, and customer. This reseach shows that to make the administration procedure more effective and efficient in the inventory, the company needs to change the employees behavior, situation, and the work mechanism between the divisions in the company.